PENGARUH TINGKAT PENDIDIKAN, PENGALAMAN USAHA, SKALA USAHA, LITERASI KEUANGAN, SOSIALISASI SAK EMKM TERHADAP PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN SAK EMKM (STUDI KASUS UMKM DI KABUPATEN SUMENEP) - Ahmad, Musleh; Dwi Yandari, Aprilya (SUSTAINABLE, 2024)
The purpose of this study was to determine the effect of education level, business experience, business scale, financial literacy, and SAK EMKM socialization on the understanding of MSME actors in preparing financial reports based on SAK EMKM in Sumenep Regency. This study uses a quantitative approach using primary data sources obtained directly from respondents in the form of answers to statements through questionnaires that have been distributed. The population in this study were all MSME actors registered at the Office of Cooperatives of Small and Medium Enterprises of Industry and Trade in Sumenep Regency. By using the slovin formula as a sampling technique with a total of 63 attempts. The data analysis method used multiple linear regression analysis with the help of the SPSS Statistics version 21 program. The results of partial test calculations stated that the variable level of education, business experience, business scale, financial literacy, and SAK EMKM socialization did not have a positive effect on MSME understanding in compiling financial reports based on SAK EMKM.